Assessing Internal Controls in Firearms Warehouse Management: A Case Study of XYZ Agency - Aristo, Yurinto; Harahap, Siti Nurwahyuningsih (E-Jurnal Akuntansi, 2024)
This study evaluates internal control practices in the management of firearms warehouses at the head office of the XYZ Agency. The research is motivated by the significant risks associated with the misuse of firearms and audit findings that reveal discrepancies in firearm records, indicating weaknesses in internal control systems. Addressing these issues is critical to ensuring accountability and effective resource management. Adopting a qualitative methodology with a case study approach, the study analyzes internal control deficiencies specific to firearms warehouse management. Data were collected through interviews, observations, and document reviews, enabling a comprehensive exploration of the subject. The analysis employed content analysis to extract meaningful insights from verbal and textual data. The evaluation framework was based on the Internal Control—Integrated Framework (COSO 2013), with a focus on the components of risk assessment and control activities. The findings reveal significant deficiencies in the internal control procedures governing firearms warehouse management. These shortcomings underscore the need for strengthened measures to mitigate risks and enhance operational effectiveness. The study offers recommendations aimed at improving internal control mechanisms and ensuring better compliance at the XYZ Agency. Additionally, the findings may serve as a valuable reference for other agencies with similar responsibilities.